Pancreatic adverse events of immune checkpoint inhibitors therapy for solid cancer patients: a systematic review and meta-analysis - Zhao, Zhe; Zhang, Weike; Pang, Longbin; Zeng, Liangjie; Liu, Surui; Liu, Jie (Frontiers in Immunology, 2023)
Abstract Objective This review aims to determine the incidence and risk of pancreatic adverse events (AEs) associated with immune checkpoint inhibitors (ICIs) therapy for solid tumors. Methods We conducted a comprehensive systematic literature search in PubMed, Embase, and Cochrane Library up to March 15, 2023, to identify all randomized controlled trials comparing ICIs with standard treatment in solid tumors. We included studies that reported immune-related pancreatitis or elevation of serum amylase or lipase levels. Following protocol registration in PROSPERO, we conducted a systematic review and meta-analysis. Results 59 unique randomized controlled trials with at least one ICI-containing arm (41 757 patients) were retrieved. The incidences for all-grade pancreatitis, amylase elevation and lipase elevation were 0.93% (95% CI 0.77-1.13), 2.57% (95% CI 1.83-3.60) and 2.78% (95% CI 1.83-4.19), respectively. The incidences for grade ≥3 pancreatitis, amylase elevation and lipase elevation were 0.68% (95% CI 0.54-0.85), 1.17% (95% CI 0.83-1.64) and 1.71% (95% CI 1.18-2.49), respectively. The use of ICIs was associated with an increased risk of all-grade pancreatic immune-related AEs (irAEs) including pancreatitis (OR=2.04, 95% CI 1.42-2.94, P =0.0001), amylase elevation (OR=1.91, 95% CI 1.47-2.49, P < 0.0001) and lipase elevation (OR=1.77, 95% CI 1.37-2.29, P < 0.0001). In addition to these, the post-hoc analysis found that PD-1 inhibitors had a significant higher risk of pancreatic AEs compared with PD-L1 inhibitors and the patients undergoing dual ICI therapy were at a significantly higher risk of pancreatic AEs than the patients receiving single ICI therapy. Conclusion Our study provides an overview of the incidence and risk of ICI-associated pancreatitis and pancreatic enzyme elevations in the treatment of solid tumors. Our findings may help raise awareness among clinicians of the potential for ICI-associated pancreatic AEs in clinical practice.